Cross-Country Study on Taxes and Public Policy in the Health Sector - Muhammad Yamin Noch; Mohammad Ridwan Rumasukun (Golden Ratio of Taxation Studies, 2024)
This study aims to comprehensively analyze the impact of taxation policies on health outcomes through a systematic review and thematic analysis of existing literature. Utilizing qualitative research methods, data were collected from academic databases, scholarly journals, and government reports using predefined search terms related to taxation policies and health outcomes. Thematic analysis was employed to identify key themes and patterns across selected studies, focusing on the effectiveness of taxation policies, the role of public policy interventions, and equity considerations. The findings suggest that taxation policies, particularly sin taxes targeting harmful products, play a significant role in shaping health behaviors and improving public health outcomes. However, the effectiveness of these policies may vary depending on contextual factors and the level of compliance. Public policy interventions, including regulatory frameworks and funding mechanisms, are crucial for maximizing the health impact of taxation policies and ensuring equitable access to healthcare services. Equity considerations are paramount in taxation policy design to mitigate socio-economic disparities in healthcare access. This research underscores the importance of cross-country comparative analyses, longitudinal studies, and interdisciplinary approaches to advance knowledge in this field and inform evidence-based policy decisions.